akdroo
contestada

G is a transformation of f. What is the formula of g in terms of f?
A. [tex]-\frac{1}{2}f(x)[/tex]
B. -2f(x)
C. f ([tex]-\frac{1}{2}x[/tex])
D. f(-2x)

G is a transformation of f What is the formula of g in terms of f A texfrac12fxtex B 2fx C f texfrac12xtex D f2x class=

Respuesta :

Answer:

C

Step-by-step explanation:

First, we can see that from f(x) to g(x), the change in x for each change in y is significantly increased. This represents a stretch in the x direction. A stretch/compression in the x direction is represented by

f(cx), with c > 1 representing a compression by c and 0 < c < 1 representing a stretch by a value of 1/c. From the vertex of each, when y changes by 1, in f(x) x changes by 2 (e.g. from x=2 to x=4), whereas in g(x) x changes by 4 (e.g. from x=-4 to x=0). Therefore, g(x) stretches x by 2, so c = 1/2, giving us

f(c(x))

= f(1/2(x))

Let's say f(a) =  f(1/2(x))

Then, because the graph stretched by 2, the vertex goes from x=2 to x=4. Our vertex is at x=-4 in g(x), so to make the vertex equal to that, we can flip f(a) around the y axis. To flip this around the y axis, we can plug -a in for a, resulting in

f (-(a))

= f(-(1/2)(x))

= g(x)

ACCESS MORE